“Bodies can be compelled; minds must be turned, since they cannot be compelled”: Preaching as an “Introduction” to Law in the Ecclesiastes of Erasmus of Rotterdam - Nowakowski, Dawid (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2021)
The recent studies on the relations between humanism or humanists and jurisprudence convince that Reneaissance, especially in XVIth century, when the national states began to raise, belonged to the periods of increased interest in the issue of law. Although Erasmus was not a layer, nor he introduced in any of his works a complete theory of law, he maintained close relations with many leading theoreticians of the law and jurists (Alciati, Budé, Cantiuncula, Zasius) and sometimes spoke in the legal discussions of his age. Among hist most important works concerning the matter of law were: Institutio principis Christiani, Ratio seu Methodus verae theologiae, Christiani matrimonii institutio, De interdicto esu carnium and Ecclesiastes. In the paper I’m going to concentrate on this latter work, in which Erasmus discusses the significance of preaching, preacher and widely understood Christian rhetoric. In the Ecclesiastes Erasmus touches the law subject with the special emphasis on historical character of law and relations between the divine law, the law of Christ and the law of Nature. After a short discussion about his understaning of law I will concentrate on the essential differentiation between the letter of law and the spirit of law, and I will point at proposed by Erasmus ways of introduction of law into human life. Erasmus, on the one hand, escaped a rigidity and abstraction of law and, on the other, he neutralised an aspect of the coercion of law. In his solution Erasmus appreciated the political dimension of preaching and acknowledged preacher as a more important guide of the people, than ruler. I’m going to interpret the Erasmian concept of preaching as an rhetorical mean of introduction of law in analogical way to “introduction” proposed by Plato in his Nomoi.